2023
DOI: 10.1017/s147474642300009x
|View full text |Cite
|
Sign up to set email alerts
|

Have Social Policy Responses to COVID-19 Been Institutionalised?

Gibrán Cruz-Martínez,
Sony Pellissery,
Ricardo Velázquez Leyer

Abstract: Countries adopted a variety of social policy responses to reduce the social risks exacerbated by the COVID-19 pandemic, which in some cases took the form of institutional reforms. The study of the institutionalisation of emergency responses is relevant to understanding if and how a critical juncture, like the one opened by the pandemic, can generate path dependencies or changes that expand or retrench social protection. This state-of-the-art article offers an overview of how social policy responses to the pand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The authorities had to intervene due to interruptions of social services and made innovations which were policy responses to deal with the situation that emerged because of the pandemic. The study investigated policy responses and changes in social services deploying the theories of institutionalism (Cruz‐Martínez et al., 2023; Hall, 1993; Hogan et al., 2022; Yuda, 2023; Yuda et al., 2022). It revealed that the nature and delivery system of social service programs had been changed due to the quick spread of COVID‐19 which was a short‐term policy response also found in many other studies (Cruz‐Martínez et al., 2023; Dorlach, 2023; Hogan et al., 2022; Yuda et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The authorities had to intervene due to interruptions of social services and made innovations which were policy responses to deal with the situation that emerged because of the pandemic. The study investigated policy responses and changes in social services deploying the theories of institutionalism (Cruz‐Martínez et al., 2023; Hall, 1993; Hogan et al., 2022; Yuda, 2023; Yuda et al., 2022). It revealed that the nature and delivery system of social service programs had been changed due to the quick spread of COVID‐19 which was a short‐term policy response also found in many other studies (Cruz‐Martínez et al., 2023; Dorlach, 2023; Hogan et al., 2022; Yuda et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The study investigated policy responses and changes in social services deploying the theories of institutionalism (Cruz‐Martínez et al., 2023; Hall, 1993; Hogan et al., 2022; Yuda, 2023; Yuda et al., 2022). It revealed that the nature and delivery system of social service programs had been changed due to the quick spread of COVID‐19 which was a short‐term policy response also found in many other studies (Cruz‐Martínez et al., 2023; Dorlach, 2023; Hogan et al., 2022; Yuda et al., 2022). Policy response‐induced interventions like advanced payment, virtual social service delivery systems, expanding coverage, and flexibility in beneficiary selection had been introduced to fight the crises caused by COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations